CBIO-04. G-QUADRUPLEX STABILIZATION ENHANCES REPLICATION STRESS AND DNA DAMAGE IN ATRX-DEFICIENT HIGH-GRADE GLIOMA. (12th November 2021) - Dharmaiah, Sharvari; Tadimeti, Vasudev; Malgulwar, Prit Benny; Alvarez, Christian; Farooqi, Ahsan; Huse, Jason
Abstract: Loss of function mutations in α-thalassaemia/mental retardation X-linked (ATRX) are a critical molecular hallmark for invariably fatal high-grade glioma (HGG). Mutational inactivation of histone chaperone ATRX leads to accumulations of abnormal DNA secondary structures known as G-quadruplexes (G4s), thereby inducing replication stress and DNA damage. As G4s arise at GC-rich regions (i.e., pericentromeric and telomeric regions), ATRX-deficiency alters genome-wide accessibility of chromatin, leads to transcriptional dysregulation, and induces alternative lengthening of telomeres (ALT). Our goal is to target ATRX deficiency through G4 stabilizers, which represent a class of novel small molecule compounds that selectively bind to and stabilize G4 structures. However, the genomic consequences and efficacy of this therapy for ATRX-deficient HGG are poorly understood. We therefore sought to evaluate the molecular mechanisms that drive selective lethality in patient-derived ATRX-deficient glioma stem cells (GSCs), following G4 stabilization. We found that ATRX-deficient GSCs demonstrate dose-dependent enhanced sensitivity to G4 stabilization, compared to ATRX-intact controls. Cell viability assays confirmed the specificity of our G4 stabilizer in comparison to other commonly used G4 stabilizers. Interestingly, G4 stabilization activated p53-independent apoptosis in ATRX-deficient GSCs. Furthermore, ATRX-deficient GSCs exhibit upregulated expression of both ATR and ATM pathways upon G4 stabilization, indicating enhanced replication stress and DNA damage via double-stranded breaks, respectively. Our preliminary findings suggest that ATR and ATM activation leads to the inhibition of transcription factor NF-κB, which in turn drives apoptosis. Lastly, our data indicate that G4 stabilization perturbs the ALT phenotype in ATRX-deficient GSCs, likely contributing to telomeric dysfunction. Taken together, these findings suggest that G4 stabilizers could synergize with ionizing radiation, the standard of care, as they are both DNA-damaging therapies. Our work defines mechanisms of action and efficacy of a novel therapeutic strategy for ATRX-deficient HGG, with strong implications for other ATRX-deficient cancers.